2012
DOI: 10.1136/bcr.02.2012.5895
|View full text |Cite
|
Sign up to set email alerts
|

Gastric GIST with synchronous neuroendocrine tumour of the pancreas in a patient without neurofibromatosis type 1

Abstract: SummaryThe gastrointestinal stromal tumours (GISTs) are the most common mesenchymal tumours of the gastrointestinal tract. These are rare tumours with an incidence of 15 new cases per million per year. The occurrence of neuroendocrine tumours of the pancreas is rare, representing 1-5% of pancreatic cancers, and it is estimated that its incidence does not exceed five to one million. GISTs are common in patients with neurofibromatosis type 1 (NF1); there are few reported cases of synchronous neuroendocrine tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Our results showed that the increased occurrence of other cancers was specific to the anatomic site and the histological type, and it had a temporal relation with the GIST diagnosis. In particular, the data pointed to the possibility of many new, clinically relevant associations between GISTs and cancers distinct from known disorders such Carney's triad/tetrad (eg, gastric GISTs, pulmonary chondromas, extra-adrenal paragangliomas, and adrenal adenomas), [27][28][29] familial GIST syndromes (eg, activating germline mutations in KIT and PDGFRa with multifocal GISTs), 3,30-33 neurofibromatosis type 1 (eg, GISTs, sarcomas, periampullary/pancreatic neuroendocrine tumors, and pheochromocytomas), [34][35][36][37][38][39] and Carney-Stratakis syndrome (eg, GISTs and paragangliomas). [40][41][42] Because sarcomas and neuroendocrine tumors, which are found in neurofibromatosis, constituted only 4.0% and 3.1% of the 1208 additional cancers, respectively, this suggests that other etiologies might be responsible for the observed trends.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the increased occurrence of other cancers was specific to the anatomic site and the histological type, and it had a temporal relation with the GIST diagnosis. In particular, the data pointed to the possibility of many new, clinically relevant associations between GISTs and cancers distinct from known disorders such Carney's triad/tetrad (eg, gastric GISTs, pulmonary chondromas, extra-adrenal paragangliomas, and adrenal adenomas), [27][28][29] familial GIST syndromes (eg, activating germline mutations in KIT and PDGFRa with multifocal GISTs), 3,30-33 neurofibromatosis type 1 (eg, GISTs, sarcomas, periampullary/pancreatic neuroendocrine tumors, and pheochromocytomas), [34][35][36][37][38][39] and Carney-Stratakis syndrome (eg, GISTs and paragangliomas). [40][41][42] Because sarcomas and neuroendocrine tumors, which are found in neurofibromatosis, constituted only 4.0% and 3.1% of the 1208 additional cancers, respectively, this suggests that other etiologies might be responsible for the observed trends.…”
Section: Discussionmentioning
confidence: 99%
“…leiomyosarcoma and osteosarcoma) and pheochromocytomas are associated with NF-1 [46 && , [47][48][49][50][51]. café au lait spots, axillary/inguinal freckling, and dermal neurofibromas) and ocular (i.e.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…This is an extremely rare condition, with only four cases, including the present case, having been reported to date (15)(16)(17) (Table). Although PNETs and GISTs arise at a frequency of 0-10% and 11-25%, respectively, in patients with NF-1 (18,19), no such cases have been reported in the literature.…”
Section: Discussionmentioning
confidence: 77%